Decadal changes in land use and land cover: impacts and their influence on urban ecosystem services - Nayak, Deeksha; Shukla, Anoop Kumar; Devi, Nandineni Rama (Aqua (London, England), 2024)
The steady growth of cities alters the urban environmental pattern and functions, posing significant challenges to urban ecological as well as environmental governance. Under this setting, analyzing the relationship between urban growth and ecological services is critical for management and policy-related sustainable urban development. The primary goal of this research is to analyse the dynamic urbanization and its influence on urban ecosystem services via changes in LULC of Mangaluru city agglomeration, India. For five decades (1980,1990, 2000, 2010, and 2022), the ecosystem service values (ESVs) are analysed using remote sensing data and Geographic Information System (GIS) techniques corresponding with the global value coefficient (VC) to estimate total ecosystem service values (ESVt) and individual ecosystem service function change. The study shows that ecosystem service values (ESVs) declined by US$ 116.89 million to US$ 85.14 million due to 9.54 and 63.44% decreases in agricultural land and wasteland/shrubland between 1980 and 2022. In terms of individual ecosystem service functions, regulating services increased from 1980 to 2022, with nutrient cycling (45.64%), raw material (15.59%), and erosion control (12.13%) contributing the most. The loss in total and certain individual ESV in the study landscape necessitates immediate action to improve urban ecosystem sustainability via proper planning and policy.